The Penn Parkinson's Daily Activities Questionnaire-15: Psychometric properties of a brief assessment of cognitive instrumental activities of daily living in Parkinson's disease. (April 2016) - Brennan, Laura; Siderowf, Andrew; Rubright, Jonathan D.; Rick, Jacqueline; Dahodwala, Nabila; Duda, John E.; Hurtig, Howard; Stern, Matthew; Xie, Sharon X.; Rennert, Lior; Karlawish, Jason; Shea, Judy A.; et al.
Abstract: Introduction: To describe the psychometric properties of the Penn Parkinson's Daily Activities Questionnaire-15 (PDAQ-15), a 15-item measure of cognitive instrumental activities of daily living for Parkinson's disease (PD) patients derived from the original 50-item PDAQ. Methods: PDAQ-15 items were chosen by expert consensus. Knowledgeable informants of PD participants (n = 161) completed the PDAQ-15. Knowledgeable informants were defined as an individual having regular contact with the PD participant. PD participants were assigned a diagnosis of normal cognition, mild cognitive impairment, or dementia based on expert consensus. Results: PDAQ-15 scores correlated strongly with global cognition (Dementia Rating Scale-2, r = 0.71, p < 0.001) and a performance-based functional measure (Direct Assessment of Functional Status, r = 0.83; p < 0.001). PDAQ-15 scores accurately discriminated between non-demented PD participants (normal cognition/mild cognitive impairment) and PD with dementia (ROC curve area = 0.91), participants with and without any cognitive impairment (normal cognition versus mild cognitive impairment/dementia, ROC curve area = 0.85) and between participants with mild cognitive impairment and dementia (ROC curve area = 0.84). Conclusions: The PDAQ-15 shows good discriminant validity across cognitive stages, correlates highly with global cognitive performance, and appears suitable to assess daily cognitive functioning in PD. Highlights: The PDAQ-15 is a brief measure of daily function dependent on cognition. It was derived from the original 50-item PDAQ. It correlates highly with measures of global cognitive abilities. It correlates highly with other existing measures of daily function. It has good discriminant validity across cognitive stages in Parkinson's disease.